Poland in the single European market: Changes in the similarity of import and export structures in comparison with the EU-10 countries in 2004-2017 - Edward Molendowski; Wojciech Polan (International Journal of Management and Economics, 2020)
It is a common knowledge that the eastern enlargement of the European Union (EU) was an extremely important undertaking for both the New Member States (EU-10) and the "old Union" countries (EU-15). One of the most important effects was significant acceleration of the development of mutual trade links, including changes in their commodity structure. In the study presented in this article, we attempted to verify the hypothesis whether, as a consequence of the eastern enlargement, the EU-10 and EU-15 markets were increasingly treated by the exporters and importers from Poland as a single market. In analyzing changes in the similarity of import and export structures, we calculated "Euclidean distance" (in 2004- 2017), the measure based on absolute differences of individual structure indices. We compared the results for Poland with the other New Member States operating on the single European market. We found that for more than a dozen years Polish exporters and importers have contributed to the increasing similarity of the structures of their respective countries' trade and the EU patterns mostly shaped by the EU-15. The results reflect the ongoing unification of the foreign trade system and its arrangement toward the recognition of both areas as a single market.
Keywords: E2; E6; F4; F5; 650; effects of EU membership; Poland; Visegrad Group; Poland against the backdrop of the Visegrad Group countries; New Member States; EU-10 countries